2006
DOI: 10.1007/s10658-006-0003-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Erwinia amylovora Strains from Croatia

Abstract: Erwinia amylovora is the causative agent of fire blight, a destructive disease of rosaceous plants. The European population can be divided into several subtypes according to differences in restriction fragment length polymorphism of the XbaI genomic DNA digest analysed with pulsed-field gel electrophoresis. This technique was also used to determine the genetic relatedness of six Croatian isolates to the E. amylovora types found in the countries surrounding Croatia. The isolates belong to the Pt2 pattern type t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Also, three E. amylovora strains from north Serbia had the Pt2 profile in this study, and all three of them were isolated near the border with Croatia. This profile was already discovered in Croatia in two separate studies (Zhang et al 1998;Halupecki et al 2006). E. amylovora was discovered in Croatia in 1995 (Cvjetković et al 1996), 6 years after it was identified in Serbia.…”
Section: Discussionsupporting
confidence: 60%
“…Also, three E. amylovora strains from north Serbia had the Pt2 profile in this study, and all three of them were isolated near the border with Croatia. This profile was already discovered in Croatia in two separate studies (Zhang et al 1998;Halupecki et al 2006). E. amylovora was discovered in Croatia in 1995 (Cvjetković et al 1996), 6 years after it was identified in Serbia.…”
Section: Discussionsupporting
confidence: 60%
“…Also, three E. amylovora strains from north Serbia had the Pt2 profile in this study, and all three of them were isolated near the border with Croatia. This profile was already discovered in Croatia in two separate studies (Zhang et al 1998;Halupecki et al 2006). E. amylovora was discovered in Croatia (Cvjetković et al 1996), 6 years after it was identified in Serbia.…”
Section: Discussionsupporting
confidence: 60%
“…Similar PFGE patterns of E. amylovora strains have been reported in countries neighbouring Serbia: Croatia, Hungary, Bulgaria and Albania. Most strains from these countries had the Pt2 pattern (Zhang et al 1998;Halupecki et al 2006), which grouped them together with the strains from Egypt and Turkey, described previously (Zhang and Geider 1997). However, strains from Serbia were not part of these studies and consequently there were no indications of the pathogen introduction directions and population origin.…”
Section: Introductionmentioning
confidence: 58%
“…Conventional laboratory methods were used for identification of isolates (Calzolari et al, 1992) and characteristic colonies were formed on D 3 medium (Kado, 1970). Halupecki et al (2006) studied the population of E. amylovora in Croatia. The isolates were obtained from different hosts in the period from 1998 to 2001.…”
Section: Croatia Occurrence and Distributionmentioning
confidence: 99%